Web sites for e-banking: a study of web sites performance in Malaysia - Goi, Chai (Academy of International Business and Economics (AIBE), 2010)
The main objective of this research is to study the performance of Web site used by commercial banks in Malaysia for E-banking. The study of Web site performance mainly focuses on two aspects, speed and problems of Web site. The analysis of Web sites is based on free Web site performance tool and Web page speed analysis online, Web Page Analyser 0.961. The study found that download time of local commercial banks’ Web site is between less than 0.01 (T1) and 245.30 seconds (14.4K). This study has identified eight major problems: TOTAL OBJECTS, TOTAL IMAGES, TOTAL SIZE, IMAGES SIZE, MULTIM SIZE, SCRIPT SIZE, HTML SIZE and CSS SIZE. Finally, the overall of performance satisfaction level is at 60%.